Accumulation of Glassy Poly(ethylene oxide) Anchored in a Covalent Organic Framework as a Solid-State Li+ Electrolyte - Zhang, Gen; Hong, You-lee; Nishiyama, Yusuke; Bai, Songyan; Kitagawa, Susumu; Horike, Satoshi (Journal of the American Chemical Society, 2019)
Design of molecular structures showing fast ion conductive/transport pathways in the solid state has been a significant challenge. The amorphous or glassy phase in organic polymers works well for fast ion conductivity because of their dynamic and random structure. However, the main issue with these polymers has been the difficulty in elucidating the mechanisms of ion conduction and thus low designability. Furthermore, the amorphous or glassy state of ion conductive polymers often confronts the problems of structural/mechanical stabilities. Covalent organic frameworks (COFs) are an emerging class of crystalline organic polymers with periodic structure and tunable functionality, which exhibit potential as a unique ion conductor/transporter. Here, we describe the use of a COF as a medium for all-solid-state Li+ conductivity. A bottom-up self-assembly approach was applied to covalently reticulate the flexible, bulky, and glassy poly(ethylene oxide) (PEO) moieties that can solvate Li+ for fast transport by their segmental motion in the rigid two-dimensional COF architectures. Temperature-dependent powder X-ray diffraction and thermogravimetric analysis showed that the periodic structures are intact even above 300 °C, and differential scanning calorimetry and solid-state NMR revealed that the accumulated PEO chains are highly dynamic and exhibit a glassy state. Li+ conductivity was found to depend on the dynamics and length of PEO chains in the crystalline states, and solid-state Li+ conductivity of 1.33 × 10–3 S cm–1 was achieved at 200 °C after LiTFSI doping. The high conductivity at the specified temperature remains intact for extended periods of time as a result of the structure’s robustness. Furthermore, we demonstrated the first application of a COF electrolyte in an all-solid-state Li battery at 100 °C.